Perceptual Responses and Future Exercise Intentions of Individuals With Systemic Arterial Hypertension. Issue 3 (June 2022) - Moreira, Mirelle Vieira; Neves, Victor Ribeiro; Schwingel, Paulo Adriano; Moreira, Sergio Rodrigues
To analyze the perceptual responses and future intentions (FI) to engage in continuous moderate aerobic exercise (CE) and high-intensity interval exercise (HIIE) of individuals with systemic arterial hypertension (SAH), we had 25 participants with SAH ( M age = 48.0, SD = 8.0 years) perform, on different days and in randomized order, 33 minute sessions of CE and 30 minutes of HIIE. Twenty seconds after each 3-minutes of these sessions, we obtained participant responses to Ratings of Perceived Exertion (RPE), the Feeling Scale (FS), the Felt Arousal Scale (FAS), and attentional focus (AF). We assessed their FI to engage in CE and HIIE at the end of each session. We analyzed results using two-way ANOVAs with repeated measures, Spearman correlation coefficients, a simple linear regression, and Wilcoxon test. We found a significant time by session type (CE and HIIE) interaction effect for RPE ( p < .001), FAS ( p = .002), and AF ( p = .004). Participants' FI to engage in HIIE were only significantly correlated with FAS ( r = −.424; p = .035) and AF ( r = .431 ; p = .032) responses. FAS responses (βz = −.455; R 2 = .207 ; p = .022) and AF responses (βz = .467; R 2 = .218; p = .019) predicted FI for engaging in HIIE. There were no significant differences in participants' FI to engage in CE sessions ( M = 76.4, SD =22.5%) versus HIIE sessions ( M = 71.8, SD = 22.9%; p = .177). Individuals with SAH had more positive perceptions of CE than HIIE, as seen by their greater dissociative AF in the CE sessions. Furthermore, these results supported the application of strategies aimed at manipulating AF in this population, possibly as a tool to increase participants' FI to engage in subsequent physical exercise.